The helper strategy in vector-transmission of plant viruses - Di Mattia, Jérémy; Zeddam, Jean-Louis; Uzest, Marilyne; Blanc, Stéphane (Peer Community Journal)

(untitled)
An intriguing aspect of vector-transmission of plant viruses is the frequent involvement of a helper component (HC). HCs are virus-encoded non-structural proteins produced in infected plant cells that are mandatory for the transmission success. Over five decades, all data collected on HCs from unrelated viral species transmitted by distinct vector species were consistent with a unique mode of action designated “the bridge hypothesis”: the HC has two functional domains, one binding the virus particle and the other binding a putative receptor in the vector, creating a reversible molecular bridge between the two. This hypothesis appeared fully satisfactory as HCs were reported solely in viruses transmitted non-circulatively -- i.e. the virus particle binds externally to the mouthpart of its vector, and can later be released therefrom and inoculated. Recently, however, HCs have also been reported in viruses transmitted circulatively, where the virus particles are internalized in gut cells and cycle within the body to reach the salivary glands. In this more complex scheme of virus-vector interaction, a simple mode of action of HC compatible with the bridge hypothesis becomes questionable. In addition, while it had consistently been shown that the sequential acquisition of HC and virus particles could only work when HC was acquired first, a recent report shows that the reverse acquisition sequence can work in some case, again questioning the bridge hypothesis as a universal mode of action. Because of the importance of HC molecules in the vector-transmission of plant viruses, we here propose an exhaustive review of the field, of its historical perspective and most recent development.